Indicators of success: measuring outcomes of evacuating pets in state and local emergency preparedness operational plans in area of economic and public health value - Arms, Anda R. (Kansas State University, 2010)
Abstract On October 6, 2006 President Bush signed the Pets Evacuation and Transportation Standards Act (PETS Act, Pub. Law No. 109-308). The Act ensures that state and local emergency preparedness operational plans address the needs of individuals with household pets and service animals following a major disaster or emergency (The Library of Congress, 109:H.R. 3858, 2006). This thesis identifies nineteen indicators to be used to evaluate the effectiveness of the PETS program in the areas of economics and public health. This report gives specific examples of how each indicator can be used to measure, assess, guide, and monitor the outcomes of evacuating pets in state or local emergency preparedness operational plans.
Keywords: Evacuating pets; Evacuation and Transportation Standards Act; Emergency planning and pets; Emergency preparedness and pets; Natural disaster and pets; Evacuation and Transportation Standards (PETS)Act and pets; Sociology, Public and Social Welfare (0630); Transportation (0709); Urban and Regional Planning (0999)